2021
DOI: 10.1002/pon.5765
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the FACIT‐Sp‐12 in a Dutch cohort of patients with advanced cancer

Abstract: Objective Although the Dutch Functional Assessment of Chronic Illness Therapy—Spiritual Well‐Being 12 Item Scale (FACIT‐Sp‐12) has been used in several Dutch studies, no study has assessed the measurement properties of the translation. The aim of this study was to perform an item‐reduction analysis, confirmatory factor analysis (CFA), test of reliability, and test of convergent validity. Methods From the baseline data of a cohort study on experienced quality of care and quality of life (eQuiPe study), 400 adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Of those, three included an exclusive or almost exclusive Muslin population [23,31,34]. The remaining seven articles included a dominant Christian population, reporting speci c breakdown of Christian sects [25,30,35,37,39,43,45]. Bai et al (2015), Daugherty et al (2005) and Whitford et al (2008) reported a small percentage of study participants who identi ed as Jewish, 7.7%, 3%, and 0.2% respectively.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Of those, three included an exclusive or almost exclusive Muslin population [23,31,34]. The remaining seven articles included a dominant Christian population, reporting speci c breakdown of Christian sects [25,30,35,37,39,43,45]. Bai et al (2015), Daugherty et al (2005) and Whitford et al (2008) reported a small percentage of study participants who identi ed as Jewish, 7.7%, 3%, and 0.2% respectively.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Previous research has pointed to the limited informative value of the total score of the FACIT-Sp-12, as the three subscales can have very different associations to other measures that become subsumed under the total score. 25,26 For example, an association between physical functioning and total SWB may only be associated to Meaning and Peace. 26 The present study therefore looked at the subscale scores instead of the total score.…”
Section: Spiritual Well-beingmentioning
confidence: 99%
“…FACIT-Sp has been utilized across a range of patient populations (e.g., cancer, elderly, heart failure) (10)(11)(12)(13) from different religions and cultures (e.g., Brazil, Italy, Japan, United States) (14)(15)(16)(17), as well as with individuals who identify as spiritual but not religious. It has been found that populations that do not have a religious affiliation score lower on the faith factor (8,18).…”
Section: Introductionmentioning
confidence: 99%
“…Since its development, FACIT-Sp has been used as a stand-alone measure of spirituality (1). It has been used as the gold standard (8) and as validation of other tools assessing spirituality and related concepts (13,18,19). Several efforts to define religion and spirituality (20)(21)(22) are underway and highlight the importance of this aspect of wellbeing and simultaneously highlight the importance of effective measurement of these constructs.…”
Section: Introductionmentioning
confidence: 99%